CogTrack: A Proof of Concept for Cognition Tracker - Yesoda Bhargava; Kanthi Kumar Kattupalli; Veeky Baths (IEEE Access)
Dementia and pathological cognitive impairment are global public health challenges. Given that there is no reliable medical cure for dementia, it is critical to develop tools that forewarn of cognitive deterioration. Usually, dementia begins 1-2 decades before symptoms manifest; this time window provides an excellent opportunity to identify cognitive deterioration early, which can enable more timely interventions. In this context, cognition tracking offers hope. The growth in wearable sensor-based devices has enabled a wide range of real-time physiological and activity metrics to be recorded. Cognition tracking is a natural progression to this growth and can prove priceless for early detection of dementia. In this work, we present a proof-of-concept of a cognition tracker, CogTrack. CogTrack is a mobile app that visualizes cognitive performance scores obtained from virtual-reality and mobile-based goal-oriented games designed and validated by us. The practical and clinical significance of CogTrack is discussed using two use cases: 1) Early indication of cognitive deterioration and 2) Tracking the impact of cognitive rehabilitation. A four-tier model is presented to illustrate the beneficiaries of CogTrack. The advantages and limitations of CogTrack are discussed in the context of available mobile applications, devices, and tools that measure cognitive performance. Additionally, we discuss how CogTrack may be advanced in the future and reflect on critical issues related to data privacy, confidentiality, ethics, scalability, and socio-medical factors which influence CogTrack adoption and acceptability. In summary, we show how an integrated system of goal-oriented games and smartphone app may be used for longitudinal cognitive assessment and tracking.